Nobiletin activates thermogenesis of brown and white adipose tissue in high‐fat diet‐fed C57BL/6 mice by shaping the gut microbiota. Issue 2 (21st January 2021) - Kou, Guangning; Li, Peiyuan; Hu, Youchun; Chen, Huanan; Nyantakyiwaa Amoah, Adwoa; Seydou Traore, Stanislav; Cui, Zhenwei; Lyu, Quanjun
Abstract: Increasing energy expenditure by activating thermogenesis in brown and beige adipocytes is a critical approach to protect against obesity. Here, we investigated the action and mechanism of a natural polymethoxyflavone on adaptive thermogenesis in high‐fat diet‐induced obesity mouse model. Nobiletin treatment significantly ameliorated obesity, alleviated the whitening of brown adipose tissue, and promoted browning of white adipose tissue in mice fed a high‐fat diet. Gut microbiota analysis and metabolomic profiling revealed that nobiletin treatment resulted in a composition shift in the gut microbiota thereby altering fermentation products acetate levels in the host feces and serum. Further, transplantation of the microbiota from nobiletin‐treated mice to microbiota‐depleted mice activated brown adipose tissue activity, promoted beige adipocytes formation, and improved high‐fat diet‐induced obesity. Our results indicate that nobiletin could be used as a dietary therapy to prevent HFD‐induced obesity, and provide a potential target‐specific gut microbial species‐driven mechanism for activating thermogenesis in brown and beige adipocytes.